Utilizing Goal Setting Strategies at the Middle Level: Helping Students Self-Regulate Behavior - Nimisha Patel; Rachel Smith; Kristen Fitzsimmons; McGee Kara; Emily Detmer (Networks: An Online Journal for Teacher Research, 2012)
For three weeks, 34 middle level students in the Midwest identified goals, completed preand post-surveys, and regularly reflected on their respective goal attainment. Quantitative and qualitative analyses revealed that participants reported increases in self-regulatory behavior.